Zebrafish embryo screen for mycobacterial genes involved in the initiation of granuloma formation reveals a newly identified ESX-1 component - Esther J. M. Stoop; Tim Schipper; Sietske K. Rosendahl Huber; Alexander E. Nezhinsky; Fons J. Verbeek; Sudagar S. Gurcha; Gurdyal S. Besra; Christina M. J. E. Vandenbroucke-Grauls; Wilbert Bitter; Astrid M. van der Sar (The Company of Biologists, 2011)
SUMMARY The hallmark of tuberculosis (TB) is the formation of granulomas, which are clusters of infected macrophages surrounded by additional macrophages, neutrophils and lymphocytes. Although it has long been thought that granulomas are beneficial for the host, there is evidence that mycobacteria also promote the formation of these structures. In this study, we aimed to identify new mycobacterial factors involved in the initial stages of granuloma formation. We exploited the zebrafish embryo Mycobacterium marinum infection model to study initiation of granuloma formation and developed an in vivo screen to select for random M. marinum mutants that were unable to induce granuloma formation efficiently. Upon screening 200 mutants, three mutants repeatedly initiated reduced granuloma formation. One of the mutants was found to be defective in the espL gene, which is located in the ESX-1 cluster. The ESX-1 cluster is disrupted in the Mycobacterium bovis BCG vaccine strain and encodes a specialized secretion system known to be important for granuloma formation and virulence. Although espL has not been implicated in protein secretion before, we observed a strong effect on the secretion of the ESX-1 substrates ESAT-6 and EspE. We conclude that our zebrafish embryo M. marinum screen is a useful tool to identify mycobacterial genes involved in the initial stages of granuloma formation and that we have identified a new component of the ESX-1 secretion system. We are confident that our approach will contribute to the knowledge of mycobacterial virulence and could be helpful for the development of new TB vaccines.